Production of flexible and electrically conductive polyethylene–carbon nanotube shish-kebab structures and their assembly into thin films - Tao, Tao (2013)
Polyethylene–multiwalled carbon nanotube shish-kebab (PE/MWCNT SK) structures with a large aspect ratio were synthesized by solvothermal growth followed by recrystallization. The effects of different crystallization temperatures (95, 105, and 115 °C) on the polymer were investigated, and the diameter of the PE crystal lamellae on the nanotubes was found to decrease with increasing crystallization temperature. Moreover, isothermal recrystallization of the SK structure at 115 °C produced crystal lamellae that were uniform in diameter, with dimensions that could be controlled by the recrystallization time. We studied also the stretchable electrical properties of uniform PE/MWCNT SK structures films on elastomer substrates under different strains. The electrical resistance of an SK/elastomer film was found to increase more slowly, compared to that of a film without the SK configuration, where an abrupt transition at a critical point was observed.